Developing sport expertise: Researchers and coaches put theory into practice (Routledge, 2008)
An athlete's development from 'ordinary' talent to elite accomplishment in sport is a long one. The emergence and fine tuning of high level sport skills takes place in increments over many years and is a journey that fascinates sport scientists, sports coaches and sports fans alike.